Core-shell hetero-phase reduced Ti–Ni–O nanotubes photoanode with enhanced optical absorption and charge transport for boosted photoelectrochemical water splitting. (3rd November 2021) - Dong, Zhenbiao; Cai, Yiqiang; Ma, Junjie; Zhang, Ke; Li, Zhenyu; Liu, Fenghua; Liu, Jibo; Lv, Fengyong; Xue, Yuan; Han, Sheng
Abstract: Bulk-phase doping and surface oxygen-defective engineering of TiO2 -based nanostructures are identified as effective routes for enhanced photoelectrochemical (PEC) water splitting. Here, we reported a reduced Ti–Ni–O nanotubes photoanode with anatase-rutile crystalline-core and oxygen vavancies amorphous-shell for boosted PEC water splitting. The core-shell hetero-phase reduced Ti–Ni–O nanotubes were fabricated through phase-structure modulation by a thermal treatment of anodized Ti–Ni–O nanotubes on Ti–Ni alloy and with one-step electrochemical reduction. Microstructure, optical and PEC measurement results confirmed effective bulk-phase Ni-doping and surface oxygen vacancies self-doping into the reduced mixed-phase Ti–Ni–O nanotubes, which enabled high capability of optical-absorption and simultaneously favored charge separation-transfer for remarkably improved the PEC water splitting. A higher photocurrent density of 1.66 mA/cm 2 at 0 V vs. Ag/AgCl and solar-to-hydrogen efficiency of 0.79% were achieved for the reduced Ti–Ni–O system, which was 5.35 and 5.27 times that of undoped TiO2, respectively. This work may shed an insight view on fabricating high-performance Ti-based nano-photoanodes with enhanced light harvesting and carrier kinetics for efficient PEC water splitting, through synergistic strategy of bulk-phase elements doping and surface oxygen vacancies self-doping. Highlights: Ti–Ni–O nanotubes with anatase-rutile mixed-phase were fabricated on Ti–Ni alloy. Oxygen vacancies (VO ) were further self-doped with one-step electrochemical reduction. Bulk-phase Ni-doping with surface oxygen-defective engineering resulted in enhanced PEC properties. Solar-to-hydrogen efficiency of the core-shell hetero-phase system was 5.27 times that of TiO2 .